The extent and barriers in providing pharmaceutical care services by community pharmacists in Malaysia: a cross-sectional study - Pengyeow Loh; Siew Siang Chua; Mahmathi Karuppannan (BMC, 2021)
Abstract Background Since the introduction of pharmaceutical care concept by Hepler and Strand in 1990, community pharmacists worldwide have been realigning their roles from being product-focused to patient-orientated to improve patient's quality of life. The objectives of this study were to determine the type of services, with emphasis on the extent of pharmaceutical care services provided by community pharmacists and the barriers in providing such services in Malaysia. Methods A cross-sectional observational study was conducted using an online questionnaire. Community pharmacists in Malaysia were invited to participate in the study via emails. The questionnaire was structured based on the Malaysian Community Pharmacy Benchmarking Guidelines, the five practice principles of pharmaceutical care by the American Pharmacists Association and other studies. The online questionnaire was opened for 6 months, from April to September 2018. A reminder to participate was sent via email to the community pharmacists every fortnight. Results A total of 420 community pharmacists responded to the online questionnaire. Besides essential services such as treatment for minor illness, medicine dispensing and counselling, most of the respondents were providing health screening and monitoring (99.5%), selection and recommendation of health supplements (90.5%), patient medication review (68.8%), weight management (52.4%) and counselling on smoking cessation (51.0%). More than half (53.3%) of the respondents reported that they were providing pharmaceutical care services to patients with chronic diseases. Based on the practice principles of pharmaceutical care, the respondents were involved in patients' data collection (23.3%), medical information evaluation (18.6%), formulating a drug therapy plan (9.3%), implementing a drug therapy plan (4.5%), and monitoring and modifying the plan (18.3%). Lack of separation between prescribing and dispensing was perceived as the main barrier to the implementation of pharmaceutical care services by a majority of the respondents (84.0%). Conclusions The present study found that pharmaceutical care services provided by community pharmacists in Malaysia were inadequate compared to international practice principles. Areas that need improvement included collaboration with patients' other health care providers; more proactive management of patient's medicine regimen; having proper patient monitoring and follow-up mechanisms, and documentation.